IDENTIFIKASI SUMBER PENDAPATAN ASLI DAERAH (PAD) KABUPATEN HALMAHERA UTARA DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH - Subandrio, Adi Suhendra (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACTIn the implementation ofregional autonomy, financial resourcesderivedfromlocal revenue (PAD) is moreimportantthan thesources ofoutsiderevenue (PAD), aslocal revenue(PAD) maybe usedin accordancewith theinitiativesandregionalinitiatives, while the form ofgovernment(non-PAD) is morebound. Opinion(PAD) is aself-sector regional revenuetaxes, levies, results oflocal state-ownedcompanies, wealthmanagementresultsinseparateareas, and otherincome of(PAD) islegitimate.In principle,theautonomous regionalgovernmentaffairsisentirely the responsibility ofthe relevant regionin terms offinancing, in accordancewith the conceptitself,which meansself-reliance. The importance ofthe financial positionof regional autonomyin thearea ofhighlyrecognized bythe government. Similarly,an alternativeway toobtainadequate financinghas also beentaken into considerationby the governmentand thepeople's representatives(DPRD). Bytrenching andincreasingrevenue (PAD) local governmentsare alsoexpectedto increaseits abilityin the administration oflocalaffairs.It is understood thatthe areaisalreadyrunningits ownaffairsaccording tothe principle ofautonomousgovernmentneeds toidentifysources oflocal revenue(PAD) to supportthe implementation ofregional autonomy. Becausethe implementation oflocal government functionswill beimplementedoptimally whenthe implementation ofgovernment affairsfollowedbyfinancialrevenue sourcesaloneareenoughareasto the regions.Keywords: Regional Revenue(PAD), Regional Autonomy